High-completed alkaline portable concrete based on industrial waste - Kovalchuk, О.; Kovalchuk, G.; Ivanychko, V. (Ways to Improve Construction Efficiency, 2019)
Designed insulation materials with a high degree of filling waste. Alkaline cements were used as alkaline substances, namely: slag-alkali cement, alkali alkali cement and alkaline portland cement, from which non-autoclaved hardening foam concrete was made, and the main calcium-containing component was blast furnace granulated slag. The resulting foam concrete based on the proposed alkaline systems are effective and in demand in the conditions of modern construction.